Application of Village Financial Management to Realize Ideal Village Finances - Nurjanti Takarini; Anajeng Esri Edhi Mahanani (Nusantara Science and Technology Proceedings, 2021)
A common obstacle felt by most villages is related to good and correct financial management. Often the stages of planning, implementation, administration, reporting, and accountability are not by the reality on the ground. What has been discussed and agreed upon together, is not followed during its implementation. The condition of village financial management in Jabung Village, Laren District, Lamongan Regency is still not optimal. This problem is due to a lack of legal understanding of village financial management. This lack of understanding is due to the socialization of village financial management laws that have not been carried out by the policy makers optimally. This consideration then strengthens the proposer to develop an android-based village financial management consulting application.